Comparison between Effectiveness of Epidural Catheter by Using Two Techniques Air Versus Saline as Pre-Emptive Analgesia in Obstetric Patients - Romana Kanwal, Riffat Saeed, Amer Latif, Tooba Ammar, Hussam Ahmad, Saeeda Rana (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In obstetric patients, epidural anaesthesia (EA) and combined spinal epidural anaesthesia (CSEA) is commonly preferred techniques due to their efficacy and acceptable safety profile with minimal adverse effects. Objective: To evaluate and compare the efficacy of epidural catheterization techniques involving the use of air versus saline for pre-emptive analgesia in obstetric patients. Study Design: Prospective study Place and Duration of Study: Department of Gynecology and Obstetrics of Sheikh Zayed Hospital Lahore from 1st January 2023 to 31st October 2023. Methodology: One hundred and thirty two patients over 18 years and younger than 38 years undergoing vaginal deliveries were selected. Patients were consecutively allocated into two distinct groups, namely Group A (LOR with air) and Group B (LOR with saline). Results: Nine patients in Group A suffered from hypotension (13.6%) and 13 patients in Group B suffered from hypotension (19.7%). Two patients in Group A developed a dural puncture and 5 patients in Group B had a dural puncture. Three patients in Group A developed PDPH and 2 patients in Group B developed PDPH which was managed conservatively. There is no significant difference in both groups regarding procedural complications. Conclusion: Epidural catheterization via loss of resistance with air (ALOR) and loss of resistance with saline (SLOR) for providing preemptive analgesia in obstetric patients show comparable analgesic effects in terms of efficacy and complications with different success rate of epidural catheter placement which was higher in the ALOR group. Keywords: Anesthesia, Catheter, Epidural, Pregnancy